Pharmacovigilance and methods of Signal Detection - Patel, Trusha (Indian Journal of Pharmacy Practice)
Pharmacovigilance serves to detect previously unrecognised adverse events associated with the use of medicines. The simplest method for detecting signals of such events is crude inspection of lists of spontaneously reported drug-event combinations. Quantitative and automated numerator-based methods like proportional reporting ratio.signal detection is important activity of pharmacovigilance for evaluating new risks of adeverse drug reactions. Signal does not establish that drug and event are causally related but suggests that further investigation may be warranted to clarify the observed association. In India there is much needed awareness about pharmacovigilance and signal detection.
Keywords: Adverse Drug Reactions; Signal; Pharmacovigilance